1977
DOI: 10.4098/at.arch.77-43
|View full text |Cite
|
Sign up to set email alerts
|

Demographic parameters and variations in numbers of the common vole

Abstract: Nabagło L., 1977: Demographic parameters and variations in numbers of the common vole. Acta theriol., 22,.Observations were made for two years of the demographic variations in two enclosed populations (A and B) of the common vole Microtus arvalis (Pallas, 1779), by means of the CMR method. Variations in numbers followed a similar course in both populations, population A reaching a lower maximum number than B. Both populations were more numerous in the second study year (1972). The greatest rate of increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…A more plausible cause for the differences in population dynamics could be related to sex ratio. In 2000, the trend in sex ratio was similar to that described by AdamczewskaAndrejewska and Nabaglo (1977), who studied a vole population in an alfalfa field. In 2000, a quite balanced sex ratio in spring was followed by a surplus of females in summer.…”
Section: Discussionsupporting
confidence: 79%
“…A more plausible cause for the differences in population dynamics could be related to sex ratio. In 2000, the trend in sex ratio was similar to that described by AdamczewskaAndrejewska and Nabaglo (1977), who studied a vole population in an alfalfa field. In 2000, a quite balanced sex ratio in spring was followed by a surplus of females in summer.…”
Section: Discussionsupporting
confidence: 79%
“…Sex ratio in common voles generally varies between trapping periods and years. For example in 2000, Briner et al (2007) found that the ratio of males and females oscillated between 1:1 and 1:2 except for September and October, when males were slightly more numerous (the trend in sex ratio was similar to that described by Adamczewska-Andrejewska & Nabaglo 1977). In 2001, males were less abundant throughout the year and in late summer females were 7-8 times more numerous than males.…”
Section: Reproduction Potential Of Microtus Arvalismentioning
confidence: 85%
“…We have shown that the enumeration method ("minimum number alive" or "calendar of catches"), a technique that has been widely used in central Europe to estimate population size of the common vole (Wojciechowska 1969, Adamczewska--Andrzejewska and Nabag³o 1977, Mackin-Rogalska 1979, Adamczewska-Andrzejewska et al 1981, Nabag³o 1981, consistently gave lower estimations of population size when compared to the JS model. The negative bias increased with density, decreased with increasing capture probability and was more pronounced in males at high density.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, the Jolly-Seber model (JS; Jolly 1965, Seber 1965) and its special model variants have turned out to be particularly useful in long-term microtine studies, as they allow estimation of population size at each sampling time as well as survival rates and birth numbers between sampling times (Pollock et al 1990). However, the capture-recapture data on common voles have been almost exclusively evaluated by means of the enumeration estimators (eg Adamczewska-Andrzejewska and Nabag³o 1977, Mackin-Rogalska 1979 yielding population size estimates, which also are known as minimum number alive (MNA; Krebs 1966) or calendar of catches (Petrusewicz and Andrzejewski 1962). Unlike the JS method, which handles recaptures within the clearly defined framework of probabilistic models based strictly on a statistical theory, the enumeration method uses recaptures only as a means of establishing that a marked individual was alive in some previous sampling period when it was caught (Pollock et al 1990).…”
Section: Introductionmentioning
confidence: 99%